Bacterial profiles of the oral, vaginal, and rectal mucosa and colostrum of periparturient sows - Virpi Piirainen; Emilia König; Aleksi Husso; Mari Heinonen; Antti Iivanainen; Tiina Pessa-Morikawa; Mikael Niku (PLoS ONE, 2025)
The commensal microbiota influences the health, feeding efficiency, and reproductive performance of sows. The microbiota composition in the alimentary and genitourinary tracts and in colostrum/milk during pregnancy and lactation also impacts the microbiota and immune system, growth, and health of the piglets. Knowledge of the microbial compositions is important for evaluation of these effects and for discovering ways to improve the health and productivity of the sows. Oral, vaginal, and rectal mucosa and colostrum were sampled from 32 sows of variable parity in late pregnancy, and colostrum within 6 hours of delivery of the first piglet, on four commercial piglet-producing farms in Finland. Microbial compositions were analyzed by 16S rRNA gene amplicon sequencing. The most abundant genera of the oral microbiota were Rothia , Moraxella , and Streptococcus . The rectal microbiota was dominated by Clostridium sensu stricto 1 . Streptococcus was the most abundant genus in the vagina and colostrum. Moderate differences in diversity and composition were observed between farms. The relative abundances of the genera Neisseria (MaAsLin 2 q = 0.002, ANCOMBC q = 0.005), Fusobacterium (MaAsLin 2 q = 0.008, ANCOMBC q = 0.04) and Bacteroides (MaAsLin 2 q < 0.005, ANCOMBC q = 0.06) were lower in oral samples and Romboutsia (MaAsLin 2 q = 0.07, ANCOMBC q = 0.05), Turicibacter (MaAsLin 2 q = 0.08, ANCOMBC q = 0.02) and Lachnospiraceae_UCG_007 (MaAsLin 2 q = 0.1, ANCOMBC q = 0.05) were higher in rectal samples of multiparous compared to primiparous sows. In vaginal samples there was a tendency of higher relative abundances of the genera Fusobacterium and Streptococcus in multiparous than primiparous sows. Among the differentially abundant taxa, F . necrophorum and F . nucleatum were identified in oral samples, F . gastrosuis and F . necrophorum in vaginal samples, and S . dysgalactiae in colostrum samples. This study provides a comprehensive overview of the mucosal and colostrum microbiota of periparturient sows during normal production conditions on Finnish commercial farms.